Effect of Equivalence Ratio on Flame Morphology, Thermal and Emissions Characteristics of Inverse Diffusion Porous Burner - A. Dekhatawala; P. V. Bhale; R. Shah (Journal of Applied Fluid Mechanics, 2024)
The diffusion porous media combustion is one possible way to eliminate the drawbacks of the existing combustion systems. Inverse diffusion flame (IDF) has features of both premixed and non-premixed flames. To integrate the advantages of porous media combustion with IDF, inverse diffusion porous (IDP) medium burner is tested for change in flame morphology and emissions at different equivalence ratio (ɸ). The porous media located at the exit of IDF burner has potential to deliver minimum flame length with low emissions. Flame appearance, flame height, flame zones etc. and emissions are experimentally investigated. Methane is used as fuel. Visible flame height is captured digitally and evaluated using ImageJ software. Central plane flame temperature is measured experimentally. CO and NOX emissions are recorded with Testo-340 flue gas analyser. The use of porous media at flame base is beneficiary in terms of achieving better air-fuel mixing and radial diffusion of air-fuel mixture. This reduces flame height with porous medium at all range of ɸ. Increase in ɸ reduces CO and enhances NOX emissions. Porous media reduces CO by 75 % and NOX by 60 %. Inverse diffusion porous medium burner emits lowest emissions in rich conditions.